2019
DOI: 10.1038/s41598-018-38452-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of PXR and CAR Polymorphisms and Antituberculosis Drug-Induced Hepatotoxicity

Abstract: A combination therapy of multiple drugs including isoniazid, rifampicin, ethambutol and pyrazinamide has been proven to be an effective option for the vast majority of tuberculosis (TB) patients. However, various adverse drug reactions (ADRs) limit its merit, with anti-TB drug-induced hepatotoxicity (ATDH) being a common and sometimes severe ADR. This study aimed to investigate the association between polymorphisms in two nuclear receptor genes, pregnane X receptor (PXR) and constitutive androstane receptor (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 52 publications
1
32
1
Order By: Relevance
“…These two hypothesized protective mechanisms are consistent with our results. In another study of the Chinese population, rs7643645 but not rs3814055 in PXR showed a statistically significant association[14]. This was somewhat different from our results.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These two hypothesized protective mechanisms are consistent with our results. In another study of the Chinese population, rs7643645 but not rs3814055 in PXR showed a statistically significant association[14]. This was somewhat different from our results.…”
Section: Discussioncontrasting
confidence: 99%
“…Overall, genetic polymorphisms of PXR may be associated with the risk of ATDILI resulting from rifampicin and isoniazid anti-tuberculosis co-therapy. Some PXR variants have been shown to increase susceptibility to ATDILI in an Indonesian population and a Chinese population, although the results were inconsistent and require further verification[1416].…”
Section: Introductionmentioning
confidence: 99%
“…for example, a single-nucleotide polymorphism (SNP) in PXR decreases risk for anti-tuberculosis druginduced hepatotoxicity [39].…”
Section: Introductionmentioning
confidence: 99%
“…19 To date, a number of studies have been conducted to investigate the potential association between NR1I2 genetic polymorphisms and the risk of ATDH, with inconsistent results being obtained. [20][21][22][23][24] For example, earlier studies from Indonesia showed that patients with the TT genotype at rs3814055 had a significantly increased risk of ATDH, 21 but another study from China reached the opposite conclusion, namely, the T allele of rs3814055 was associated with a decreased risk for ATDH. 20 However, a systematic review and meta-analysis can be used to pool results from different studies, thereby enhancing the precision of estimates of treatment effects.…”
Section: Introductionmentioning
confidence: 99%